Terahertz Spin‐to‐Charge Current Conversion in Stacks of Ferromagnets and the Transition‐Metal Dichalcogenide NbSe2. Issue 36 (20th October 2022) - Nádvorník, Lukáš; Gueckstock, Oliver; Braun, Lukas; Niu, Chengwang; Gräfe, Joachim; Richter, Gunther; Schütz, Gisela; Takagi, Hidenori; Zeer, Mahmoud; Seifert, Tom S.; Kubaščík, Peter; Pandeya, Avanindra K.; et al.
Abstract: Transition‐metal dichalcogenides (TMDCs) are an aspiring class of materials with unique electronic and optical properties and potential applications in spin‐based electronics. Here, terahertz emission spectroscopy is used to study spin‐to‐charge current conversion (S2C) in the TMDC NbSe2 in ultra‐high‐vacuum‐grown F|NbSe2 thin‐film stacks, where F is a layer of ferromagnetic Fe or Ni. Ultrafast laser excitation triggers an ultrafast spin current that is converted into an in‐plane charge current and, thus, a measurable THz electromagnetic pulse. The THz signal amplitude as a function of the NbSe2 thickness shows that the measured signals are fully consistent with an ultrafast optically driven injection of an in‐plane‐polarized spin current into NbSe2 . Modeling of the spin‐current dynamics reveals that a sizable fraction of the total S2C originates from the bulk of NbSe2 with the opposite, negative sign of the spin Hall angle as compared to Pt. By a quantitative comparison of the emitted THz radiation from F|NbSe2 to F|Pt reference samples and the results of ab initio calculations, it is estimated that the spin Hall angle of NbSe2 for an in‐plane polarized spin current lies between ‐0.2% and ‐1.1%, while the THz spin‐current relaxation length is of the order of a few nanometers. Abstract : Transition‐metal dichalcogenides (TMDCs) are an aspiring class of materials with unique electronic and optical properties and potential applications in spintronics. By terahertz emission spectroscopy, it is found that photoexcitation induces significant ultrafast spin injection into and spin‐to‐charge current conversion in NbSe2 . A spin‐current model allows us to quantitatively estimate the spin Hall angle and the terahertz spin‐current relaxation length of NbSe2 .